The development of concepts in science: A survey of junior secondary pupils in Barbados - Adey, Philip S. (Ministry of Education, 1977)
Two class tasks were administered to a sample of pupils, aged 11-17 years from one selective and two non-selective schools in Barbados, to assess average levels of cognitive development. Results are presented by age and by school year. In the selective school, virtually all students were at least at the late concrete operational stage, while the percentage at the early formal operational stage rose from about 25 percent of 13-year-olds to about 75 percent of 16-year-olds. About 15 percent in the 11+ age group in the non-selective schools were still pre-operational. The overall difference was highly significant in favour of boys and three hypotheses are proposed to explain this difference. A tentative analysis of the conceptual levels demanded by the West Indian Science Curriculum indicated a mismatch between curriculum demands and the cognitive levels in the schools. The methodology of curriculum analysis needs to be validated further
Keywords: West Indian Science Curriculum